Hyperoside nanocrystals for HBV treatment: process optimization, in vitro and in vivo evaluation. (1st November 2016) - Shen, Baode; Wu, Na; Shen, Chengying; Zhang, Fucheng; Wu, Yan; Xu, Pinghua; Zhang, Lihong; Wu, Wei; Lu, Yi; Han, Jin; Wang, Yonggang; Yuan, Hailong
Abstract: The aim of this study was to develop hyperoside (Hyp) nanocrystals to enhance its dissolution rate, oral bioavailability and anti-HBV activity. Hyp nanocrystals were prepared using high pressure homogenization technique followed by lyophilization. A Box–Behnken design approach was employed for process optimization. The physicochemical properties, pharmacokinetics and anti-HBV activity in vivo of Hyp nanocrystal prepared with the optimized formulation were systematically investigated. Hyp nanocrystals prepared with the optimized formulation was found to be rod shaped with particle size of 384 ± 21 nm and PDI of 0.172 ± 0.027. XRPD studies suggested slight crystalline change in drug. Dissolution rate obtained from Hyp nanocrystals were markedly higher than pure Hyp. The nanocrystals exhibited enhanced Cmax (7.42 ± 0.73 versus 3.80 ± 0.66 mg/L) and AUC0 − t (193.61 ± 16.30 versus 91.92 ± 17.95 mg· h/L) with a 210.63% increase in relative bioavailability. Hyp nanocrystals exhibited significantly greater anti-HBV activity than Hyp. These results suggested that the developed nanocrystals formulation had a great potential as a viable approach to enhance the bioavailability of Hyp.